2021
DOI: 10.1039/d1np00001b
|View full text |Cite
|
Sign up to set email alerts
|

Solanum steroidal glycoalkaloids: structural diversity, biological activities, and biosynthesis

Abstract: Chemical structures of typical Solanum steroidal glycoalkaloids from eggplant, tomato, and potato.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 184 publications
(500 reference statements)
3
67
0
5
Order By: Relevance
“…For the Cluster 1 plants (S. melanocerasum, S. nigrum, and S. retroflexum), the primary glycoalkaloids present in all plants were 15, 17, 20, 28, and 46. In the Cluster 2 plants, three predominant compounds (16, 17, and 26) that belong to solanidine-type glycoalkaloids were present across all the species [19,34]. The clustering is consistent with the fact that S. nigrum, S. retroflexum, and S. melanocerasum belong to the Morelloid clade and have been shown to be genetically related based on morphological and molecular data [40,41].…”
Section: Glycoalkaloids Clustering In Solanum Plantssupporting
confidence: 72%
See 3 more Smart Citations
“…For the Cluster 1 plants (S. melanocerasum, S. nigrum, and S. retroflexum), the primary glycoalkaloids present in all plants were 15, 17, 20, 28, and 46. In the Cluster 2 plants, three predominant compounds (16, 17, and 26) that belong to solanidine-type glycoalkaloids were present across all the species [19,34]. The clustering is consistent with the fact that S. nigrum, S. retroflexum, and S. melanocerasum belong to the Morelloid clade and have been shown to be genetically related based on morphological and molecular data [40,41].…”
Section: Glycoalkaloids Clustering In Solanum Plantssupporting
confidence: 72%
“…Compounds 15 and 17 were identified against the analytical standards for solamarine and solamargine, respectively. Compounds 1 and 29 were identified as isomers of hydroxysolamargine based on the molecular ion [M + H] + of 884.50 and the aglycone fragment of 430.33, which corresponds to hydroxylated solasodine [19]. Hydroxy-solamargine was previously reported in the fruits of S. nigrum, as well as in S. melongena, in correlation with solamargine [17,18].…”
Section: Glycoalkaloids Assignmentmentioning
confidence: 96%
See 2 more Smart Citations
“…3b and Table 1), respectively [21]. Alpha-tomatidine was composed of a tomatidine aglycone unit glycosylated by four monosaccharides which included d-galactose, 2 × d-glucose and d-xylose, whereas tomatidine galactoside contained d-galactose as a saccharide [22]. Therefore, this indicated that the transition from m/z 1034 to m/z 578, which is alpha-tomatine to tomatidine galactoside, occurred with the loss of 3 monosaccharaides which consisted of 2 × d-glucose and d-xylose.…”
Section: Resultsmentioning
confidence: 99%